TINJAUAN HUKUM ISLAM TERHADAP PENGAWASAN TAMAN NASIONAL KERINCI SEBLAT DALAM UPAYA PELESTARIAN LINGKUNGAN HIDUP DI KABUPATEN KERINCI - Pitriani Pitriani; Nurasiah Nurasiah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2018)
Abstract: The environment in Islamic teachings is rooted in the Qur'an. The approach used in this study is sociological juridical. The sample technique that the researcher used in this study was purposive sampling. After the data is classified then analyzed qualitatively, the analysis is not based on mathematical calculations but underlies the reality that is in the field then described in the form of reality. The results of this study include: 1) Human relations as caliphs on earth to their environment must be based on the principle of correct use and avoiding damage. 2) Monitoring of the TNKS forest has not been implemented effectively, this can be known, where there are still activities that can damage the TNKS forest such as encroachment, theft of forest products, illegal logging in the TNKS forest. 3) Constraints in the preservation and supervision of KSNP in Kerinci Regency are: a) constraints that there are still people who do not understand the importance of TNKS forests; b) field conditions or TNKS forests that are easily accessible to encroachers, illegal loggers and theft of forest products; c) lack of officers overseeing the TNKS forest; and d) lack of facilities and infrastructure.